ANALISIS EFEKTIVITAS PELAKSANAAN PINJAMAN DANA BERGULIR PADA BADAN USAHA MILIK DESA (BUMDES) BERSAMA KECAMATAN BAYAN (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine the effectiveness of the revolving fund when viewed from the accuracy of the borrower's targets and the appropriate appropriateness of the Women's Group Loans, and to determine the effectiveness level of the revolving fund revenues from the January-December 2016 fiscal year.The data analysis used in this research is using Likert scale, and calculate the ratiobetween target projection rate and revolving rate of revolving fund loan in January-December 2016 period.Based on the distribution of respondents'answers, the number of scores obtained to evaluate the effectiveness of the revolving fund in Bumdes Bersama Kecamatan Bayan is = 6111. This result is obtained from the sum of all respondents' scores through 15 questionnaires about the effectiveness of the revolving fund loan at Bumdes Bersama Kecamatan Bayan. Thus, the effectiveness when viewed from the results of respondents is =6111: 7425 = 81% of the predefined criteria. Included in the category is very effective. Based on the calculation of the comparison between the target and the realization that the realization rate of loan repayment during 2016 reached 48%. Percentage 48% included in category strong enough / quite effective. Thus, it can be concluded that the effectiveness of the implementation of revolving fund loans when viewed from the loan repayment rate is quite effective. This is caused by arrears that have not been fully collected